DAMPAK METODE PELATIHAN KECEPATAN TERHADAP KEMAMPUAN LARI 100 METER PADA REMAJA BERUSIA 16-17 TAHUN DI KOTA SERANG - Faisal Hanif; Desty Endrawati Subroto; Melani Agustina; Ahdi Muhyi; Alfian Dikri; Rijki Rahmatullah (Jurnal Padamu Negeri, 2025)
This study aims to analyze the effect of speed training methods on 100-meter running ability in adolescents aged 16-17 years in Serang City. The background of this study is the importance of speed training in improving running performance, especially in adolescents who are growing. The purpose of this study was to determine the significant effect of various speed training methods on 100-meter running time. This study used a quasi-experimental design with a control group, which involved measurements before and after training. The study sample consisted of 100 adolescents (50 people in the experimental group and 50 people in the control group). The experimental group followed a speed training program that was arranged for eight weeks, while the control group continued their usual physical activities. The results showed a significant increase.